PENGARUH HARGA MINYAK, HARGA EMAS, TINGKAT SUKU BUNGA, DAN JUMLAH UANG BEREDAR TERHADAP INDEKS HARGA SAHAM GABUNGAN DIBURSA EFEK INDONESIA (BEI) PERIODE 2011-2015 - Irma Lina Fadila Husna Putri; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2017)
This research conducted to analyze the effect of Oil Prices, Gold Price, Interest Rate, and the Circulation of Money toward Composite stock price index or IHSG in Indonesian Stock Exchange (IDX). The research used time period for about five years, start from 2011 and ends in 2015. The kind of the data which is used in the research is data time series that belongs to Composite stock price index or IHSG in Indonesian Stock Exchange (IDX). The research is using secondary data. The methodology of analyzing data is doubled regression. Based on the analysis it can be concluded that a) The Oil Prices has no effect toward IHSG. b) Gold Price has effect toward IHSG. d) Interest Rate has no effect in IHSG. d) The circulation of money has no effect in IHSG.